The agent takes the stage. (12th November 2009) - Anstey, Josephine; Seyed, A. Patrice; Bay-Cheng, Sarah; Pape, Dave; Shapiro, Stuart; Bona, Jonathan; Hibit, Stephen
The deployment of virtual characters in intermedia performance drives divergent agendas of this research group. From the perspective of performance studies, we examine the effect of computer-based characters as actors and believe explorations of mediated agency can open up new forms of engagement for live productions. From the visualisation point of view, we are interested in how abstraction and animation techniques, based on motion tracking and procedural methods, convey character and warp and extend the gestural repertoire of a human actor. In terms of interactive drama, we are working on stream of consciousness characters: algorithmically recombining text to create a psychological entity with an autonomous inner structure. From an artificial intelligence perspective, we investigate how to design and use intelligent agents as actors. These agendas reflect an odd mix of aesthetic and technical concerns, and rightly so, as they are driven by the different goals of our interdisciplinary team.